The Impassibility of God - Pollard, T. E. (Scottish journal of theology, 1955)
‘It becomes theologians to be cautious in accepting the gifts of the Greeks.’ It is the conviction of the present writer that Christian theology as a whole, and the doctrine of God in particular, have suffered because of the lack of caution which theologians in every age have shown in their too ready acceptance of the gifts which the Greeks have brought. Of no age is this more true than of that which witnessed the formalisation and systematisation of the Christian doctrine of the Godhead, namely, the second, third and fourth Christian centuries, during which ‘theologizing’ was for the most part in the hands of men who had been trained in the philosophical schools of the Hellenistic world, and who refused to do intellectually what Justin Martyr had refused to do literally, refused, that is, to doff the academic dress of the philosopher. But it is still true that philosophical theologians today, in their desire to interpret the Christian faith in modern philosophical terms, tend to be too ready to accept as gifts the presuppositions of some modern philosophical school, and in doing so to give away much that is vital to the faith which they are seeking to interpret.